Optimal usage of unicompartmental knee arthroplasty: a study of 41,986 cases from the National Joint Registry for England and Wales. - Liddle, A; Pandit, H; Judge, A; Murray, D (2015)
Unicompartmental Knee Replacement (UKR) has advantages over Total Knee Replacement (TKR) but National Joint Registries (NJRs) report a significantly higher revision rate for UKR. As a result, most surgeons are highly selective, offering UKR to only a small proportion (≤5%) of patients requiring knee replacement and consequently performing very few each year. However, surgeons with large UKR practices have the lowest revision rates. Overall practice size is often beyond the surgeon’s control and so case volume may only be increased by broadening indications, and offering UKR to a greater proportion of knee replacement patients. The aim of the study was to determine the optimal UKR usage (defined as the percentage of knee replacement practice comprised by UKR) to minimise the revision rate in a sample of 41,986 records from the NJR for England and Wales. UKR usage has a complex, non-linear relationship with revision rate. Optimal results are achieved with usage between 40-60%. Surgeons with the lowest usage (≤5%) have the highest revision rates. With optimal usage, using the most frequently-used implant, 5 year survival is 96%, compared with 90% with low usage (≤5%) previously considered ideal. The revision rate of UKR is highest if narrow indications are used. The widespread use of broad indications, using appropriate implants, would give patients the advantages of UKR, without the high reported revision rate.